Healthcare providers' role in providing sexual and reproductive health information to people with intellectual and developmental disabilities: A qualitative study. Issue 4 (1st February 2021) - Schmidt, Elizabeth K.; Beining, April; Hand, Brittany N.; Havercamp, Susan; Darragh, Amy
Abstract: Background: Individuals with intellectual and developmental disabilities demonstrate disparities in sexual and reproductive health (SRH) compared to individuals without disabilities (e.g., lack of sexual education and knowledge, increased rates of abuse, unplanned pregnancies and sexually transmitted infections). Therefore, the purpose of this study was to identify topics healthcare providers address and perceived barriers and supports to SRH education. Methods: We conducted semi‐structured interviews with healthcare providers ( N  = 12). Results: Providers address relationships, safety, protection and appropriate sexual behaviours with clients with intellectual and developmental disabilities. Parent education and client‐centred care were identified as supports, while the patient's level of understanding, the provider's lack of knowledge or access to resources and to appropriate referrals were identified as barriers to SRH education. Conclusion: Future studies are needed to link providers to resources they can use to provide comprehensive, accessible SRH education for clients with intellectual and developmental disabilities.